Hypereosinophilia presented as thromboembolic event: a rare manifestation - Atri, Sudhir K.; ., Homdutt; Goel, Manjri; Yadav, Devender (International Journal of Research in Medical Sciences, 2020)
Eosinophilia refers to peripheral blood absolute eosinophil count above the ULN, normal range of AEC is 0.05-0.5× 109/l (1-6%). Hyper eosinophilia refers to AEC above 1.5×109/l. Hypereosinophilia can affect multiple organs and can cause cardiomyopathy, gastroenteritis, cutaneous lesions, pneumonitis, and neuritis. In addition, some patients develop thromboembolic complications. We are presenting a case who presented to us with thromboembolic complication later diagnosed as hypereosinophilia with Bone marrow showing myeloid associated eosinophilia (Primary eosinophilia).